Impact of wars and natural disasters on emerging and re-emerging infectious diseases - Topluoglu, Seher; Taylan-Ozkan, Aysegul; Alp, Emine (Frontiers in Public Health, 2023)
Emerging Infectious Diseases (EIDs) and Re-Emerging Infectious Diseases (REIDs) constitute significant health problems and are becoming of major importance. Up to 75% of EIDs and REIDs have zoonotic origin. Several factors such as the destruction of natural habitats leading humans and animals to live in close proximity, ecological changes due to natural disasters, population migration resulting from war or conflict, interruption or decrease in disease prevention programs, and insufficient vector control applications and sanitation are involved in disease emergence and distribution. War and natural disasters have a great impact on the emergence/re-emergence of diseases in the population. According to a World Bank estimation, two billion people are living in poverty and fragility situations. Wars destroy health systems and infrastructure, curtail existing disease control programs, and cause population movement leading to an increase in exposure to health risks and favor the emergence of infectious diseases. A total of 432 catastrophic cases associated with natural disasters were recorded globally in 2021. Natural disasters increase the risk of EID and REID outbreaks by damaging infrastructure and leading to displacement of populations. A Generic National Action Plan covering risk assessment, mechanism for action, determination of roles and responsibilities of each sector, the establishment of a coordination mechanism, etc. should be developed.